(3ELGRI ef GdYGQa HGddg YHOGdQMef Hf eMeO GdaGSi dCHj eMeO YHOGddg Hf eMeO GdYjGTjs - (3YHO Gddg Hf eMeO Hf CHj HcQ GdYjGTj, CHh SGde,J (B1090 (3g` s ((3YHO GdQMef Hf eMeO GdaGSi s)
(3ChdgG (B:s
(3hHYO , abO SCdfi GdCQjH CHh eMeO YHOGddg Hf Gdabjg CHj YHOGddg eMeO GdYjGTj Cf CLjRg aj GdUMjMjf HYO bQGAJg Ydi UOQgeG aCLHJg deG WdH s
(3BNQgG (B:s
(3hdjcf gPG BNQ eGQSefGg ef gPg GdYLGdI YQafG Gddg NjQg hhbGfG VQg Hefg hGfJgi ef NWg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B185 - (3U(B189s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B129 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B112s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B15 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs